2019
DOI: 10.21203/rs.2.10032/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postprandial transfer of colostral extracellular vesicles and their protein and miRNA cargo in neonatal calves

Abstract: Background Extracellular vesicles (EVs) such as exosomes are key regulators of intercellular communication that can be found in almost all bio fluids. Although studies in the last decade have made great headway in discerning the role of EVs in many physiological and pathophysiological processes, the bioavailability and impact of dietary EVs and their cargo still remain to be elucidated. Due to its widespread consumption and high content of EV-associated microRNAs and proteins, a major focus in this field has b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…In particular, it was confirmed that EVs and their cargo were not degraded in the harsh digestive environment encountered when milk EVs were ingested (Benmoussa et al, 2016;Izumi et al, 2012;Shandilya et al, 2017;Zeng et al, 2019). It was also confirmed in vitro (Hansen et al, 2020;Izumi et al, 2015;Maburutse et al, 2017;Rani et al, 2017;Roerig et al, 2021;Wolf et al, 2015), in vivo (Kirchner et al, 2020;Manca et al, 2018), or under both conditions (Lopez de Las Munagala et al, 2016) that these EVs and their cargo are taken up (Fig. 1D).…”
Section: Uptake/stabilitymentioning
confidence: 61%
“…In particular, it was confirmed that EVs and their cargo were not degraded in the harsh digestive environment encountered when milk EVs were ingested (Benmoussa et al, 2016;Izumi et al, 2012;Shandilya et al, 2017;Zeng et al, 2019). It was also confirmed in vitro (Hansen et al, 2020;Izumi et al, 2015;Maburutse et al, 2017;Rani et al, 2017;Roerig et al, 2021;Wolf et al, 2015), in vivo (Kirchner et al, 2020;Manca et al, 2018), or under both conditions (Lopez de Las Munagala et al, 2016) that these EVs and their cargo are taken up (Fig. 1D).…”
Section: Uptake/stabilitymentioning
confidence: 61%
“…Second, an imbalanced absorption of vesicle subpopulations within the colostrum. Other tissues were not analyzed for the presence of milk-derived miRNAs ( 233 ). Hence, the transfer of maternal miRNAs into the neonatal systemic circulation remains elusive and a highly discussed topic, which still needs further investigation.…”
Section: The Importance Of Breast Milk For the Development Of The Neonatementioning
confidence: 99%